2002
DOI: 10.1046/j.1442-2042.2002.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Does transurethral resection of the prostate facilitate detection of clinically significant prostate cancer that is missed with systematic sextant and transition zone biopsies?

Abstract: Background : A prospective study was conducted to determine whether transurethral resection of the prostate (TURP) facilitates detection of prostate cancer that is missed with systematic sextant biopsies associated with transition zone (TZ) biopsies. Methods : A total of 139 consecutive patients underwent transperineal TZ biopsies of each lobe in addition to a transrectal systematic sextant peripheral zone (PZ) biopsy. Patients whose biopsies were negative for cancer received TURP for relief of lower urinary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…Previously, we reported the results of transrectal 6-core biopsy from the PZ and transperineal 2-core biopsy from the TZ. No cancers were detected in the TZ alone (20). In contrast, Ishizuka et al reported that the cancer detection rate in the TZ alone was relatively high (8%) with transrectal sextant and four additional TZ biopsies (21).…”
Section: Discussionmentioning
confidence: 90%
“…Previously, we reported the results of transrectal 6-core biopsy from the PZ and transperineal 2-core biopsy from the TZ. No cancers were detected in the TZ alone (20). In contrast, Ishizuka et al reported that the cancer detection rate in the TZ alone was relatively high (8%) with transrectal sextant and four additional TZ biopsies (21).…”
Section: Discussionmentioning
confidence: 90%
“…While TURP can frequently detect cancer even in cases with negative biopsies, it may reveal that some of the cancers are clinically insignificant, as postulated in a study by Kitamura et al [14]. They detected small-volume cancer in 2 of 18 patients who underwent radical prostatectomy after TURP (0.49 and 0.36 cm 3 ).…”
Section: Discussionmentioning
confidence: 84%
“…Greene showed that transition zone PCa is frequently associated with larger and high-grade PCa in the peripheral zone [23]. Furthermore a subset of PCas located in the transition zone can be aggressive [24][25][26]. To date, there have been no studies investigating the diagnostic yield of PCa in men with minor LUTS [27,28].…”
Section: Discussionmentioning
confidence: 96%